Intraoperative Transillumination to Determine the Extent of Frontal Sinus in Subcranial Approach to Anterior Skull Base - Sharan, Rajeev (Thieme Medical Publishers, 2011)
We sought to determine the extent of the frontal sinus by intraoperative transillumination through the superomedial orbital wall in a subcranial approach to the anterior skull base. After raising a bicoronal flap, the frontal sinus was transilluminated through the superomedial orbital wall with a fiber-optic light source, delineating the extent of the frontal sinus. The frontal sinus boundary was marked with a marker pen. A frontal sinus anterior wall osteotomy was performed with a sagittal saw, staying within the confines of the frontal sinus marking. A bone flap was removed, and the posterior wall was drilled out. The remaining procedure was performed in a standard fashion. At the end of the procedure, the bone flap was fixed with a titanium plate. A total of 58 patients had undergone craniofacial resection from January 2004 to December 2007. In 13 patients, a subcranial approach was employed using the transillumination technique. Transillumination was successful in delineating the frontal sinus periphery in all 13 patients. Intraoperative transillumination of the frontal sinus through the superomedial orbital wall is a simple and effective method to delineate the frontal sinus periphery in a subcranial approach to the anterior skull base.